Development of a Searchable System to Confirm MR Imaging Safety Information for Implantable Medical Devices - Fujiwara, Yasuhiro (Magn Reson Med Sci, 2019)
The purpose of this study was to develop a searchable system to confirm magnetic resonance (MR) safety information of implantable medical devices (IMDs) to safely perform magnetic resonance imaging examinations. We labeled MR safety information for IMDs based on package insert descriptions and then categorized allowed MR conditions for IMDs. Finally, a searchable system was developed to use the database via the internet. This system enables efficient and accurate confirmation of MR safety information for IMDs.